The Use of Real-Time Quaking-Induced Conversion for the Diagnosis of Human Prion Diseases - Poleggi, Anna; Baiardi, Simone; Ladogana, Anna; Parchi, Piero (Frontiers in Aging Neuroscience, 2022)
Prion diseases are rapidly progressive, invariably fatal, and transmissible neurodegenerative disorders associated with the accumulation of the amyloidogenic form of the prion protein in the central nervous system. In humans, prion diseases are highly heterogeneous both clinically and neuropathologically. Prion diseases are challenging to diagnose as many other neurologic disorders, especially at clinical onset, share the same symptoms. Definitive diagnosis requires brain autopsy to identify the accumulation of the pathological prion protein, which is the only specific disease biomarker. Although brain post-mortem investigation remains the gold standard diagnostic tool, antemortem clinical, instrumental, and laboratory tests showing variable sensitivities and specificity, being surrogate disease biomarkers, are routinely performed to reach a diagnosis. In the last decade, the ultrasensitive Real-Time Quaking-Induced Conversion (RT-QuIC) assay, exploiting the detection of misfolded prion protein through an amplification strategy, has highly improved the “in-vitam” diagnostic process, reaching in cerebrospinal fluid and olfactory mucosa around 96% sensitivity and virtually 100% specificity. RT-QuIC also improved the detection of disease-specific misfolded prion protein in several peripheral tissues, possibly even before the clinical onset of the disease. The latter aspect is of great interest for the early and even preclinical diagnosis in subjects at genetic risk of developing the disease, who will likely be the main target population in future clinical trials. In this review, we present an overview of the current knowledge and future perspectives on the use of RT-QuIC to diagnose human prion diseases.